External Hemorrhage from a Portacaval Anastomosis in a Patient with Liver Cirrhosis. (8th July 2014) - Biyik, Murat; Ucar, Ramazan; Cifci, Sami; Ozbek, Orhan; Gungor, Gokhan; Ozer Cakir, Ozlem; Yavuz, Fatma; Ataseven, Huseyin; Demir, Ali
Abstract : Variceal bleeding is the major complication of portal hypertension in patients with liver cirrhosis. Hemorrhage mainly occurs in gastrointestinal lumen. Extraluminal hemorrhages are quite rare, such as intraperitoneal hemorrhages. We aimed to present a variceal bleeding case from the anastomosis on the anterior abdominal wall, as an extraordinary bleeding location, in a patient with portal hypertension in whom there were no esophageal and gastric varices.